Der Gott der Lebendigen Eine biblische Gotteslehre - Feldmeier, Reinhard (Mohr Siebeck, 2017)
The God of the Living. A Biblical Doctrine of God. 2 ndrevised and bibliographically supplemented edition.
PublicationDate: 20170713
Keywords: Gott -- Biblische Theologie -- Gotteslehre -- Studienliteratur -- Altes Testament -- Neues Testament -- Studienliteratur - Theologie -- Textbooks - Theology -- Array